Impact of pre-equilibration and diffusion limited release kinetics on effluent concentration in column leaching tests: Insights from numerical simulations. (May 2017) - Finkel, Michael; Grathwohl, Peter
Highlights: Approx. 6000 numerical equilibration and column leaching test experiments. Multi-spherical diffusion model to describe release kinetics of grain size mixtures. Systematic analysis of a large spectrum of solid material and solute properties. Equilibration time decreases with sorption coefficients and increases with grain size. Initial conditions only sensitive if release kinetics is slow. Abstract: Column leaching tests have become a standard method for assessing leaching of pollutants from materials used, e.g., for road and railway constructions and in landscaping measures. Column tests showed to be practical in laboratories yielding robust and reproducible results. However, considerable uncertainty still exists related particularly to the degree of equilibration of the pore water with the solids during preparation (pre-equilibration) and percolation of the column. We analyse equilibration time scales and sensitivity of concentrations in column leachate with respect to initial conditions in a series of numerical experiments covering a broad spectrum of material and solute properties. Slow release of pollutants from solid materials is described by a spherical diffusion model of kinetic sorption accounting for multiple grain size fractions and sorption capacities. Results show that the cumulative concentrations are rather independent of the pre-equilibration level for a broad spectrum of parameter settings, e.g. if intra-particle porosity is high, grain size is small, or if the sorption coefficient is large. Sensitivity increases with decreasing liquid solid ratios and contact time during percolation. Significant variations with initial column conditions are to be expected for material and compound properties leading to slow release kinetics. In these cases, sensitivity to initial conditions may have to be considered.